The Absurdity of Existence: Analyzing Human Relationships in Sartre's No Exit - Abdalla, Shabaz; Mohammed, Rebwar Zainalddin; Ahmad, Hedayat Muhamad (Balai Bahasa Kalimantan Tengah, 2024)
This article explores the philosophical concepts of existentialism and absurdism, focusing on the works of Jean-Paul Sartre and Albert Camus. It begins by examining Sartre's notion of